2021
DOI: 10.1038/s41598-021-83747-3
|View full text |Cite
|
Sign up to set email alerts
|

Testing for phylogenetic signal in claws suggests great influence of ecology on Caribbean intertidal arthropods (Acari, Oribatida)

Abstract: Claws are common biological attachment devices that can be found in a wide variety of animal groups. Their curvature and size are supposed to be parameters related to ecological aspects. Mites, known as very small arthropods, occupy a wide range of ecological niches and are a perfect model system to investigate correlations of claw morphology with ecology. There is only one study regarding this question in littoral mites but the phylogenetic impact, which plays an important role in the evolution of morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Littoral oribatid mites possess claws nearly twice the size compared to their terrestrial counterparts. This pronounced difference between littoral and terrestrial mites, with aquatic and semiaquatic species falling in between, resonates with previous findings on claw shape and microhabitat relationships in intertidal mites 24 , 25 , 41 . The extreme conditions of the intertidal zone with the moving tidal water, faced by littoral species, have largely influenced this unique adaptation of having considerably larger claws 24 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Littoral oribatid mites possess claws nearly twice the size compared to their terrestrial counterparts. This pronounced difference between littoral and terrestrial mites, with aquatic and semiaquatic species falling in between, resonates with previous findings on claw shape and microhabitat relationships in intertidal mites 24 , 25 , 41 . The extreme conditions of the intertidal zone with the moving tidal water, faced by littoral species, have largely influenced this unique adaptation of having considerably larger claws 24 .…”
Section: Discussionsupporting
confidence: 91%
“…The tidal zones, these mites inhabit, subject them to the relentless forces of tidal water movements, which in turn have driven the evolution of their claw morphology to optimize movement and attachment. The strong evolutionary pressure in this extreme environment even has led to the loss of a phylogenetic signal in the claws of intertidal oribatid mites 25 . However, recent initial studies on claws of a few typical terrestrial oribatid mite species 26 , 27 indicated that habitat specificity and lifestyle also have an impact on claw morphology in the terrestrial environment, but this correlation is apparently weaker than in intertidal oribatid mites which are subject to strong external forces.…”
Section: Introductionmentioning
confidence: 99%
“…For the target species Fortuynia atlantica, we compared the shape of the first leg claw of 11 males and 15 females. Geometric morphometric data analyzed in this study is from Pfingstl et al (2020) and Kerschbaumer and Pfingstl (2021) and is stored at Dryad; methods are given in the respective publication. Data analysis was done in Rstudio vers.…”
Section: Methodsmentioning
confidence: 99%
“…Geometric morphometrics have been successfully utilized to investigate the evolutionary processes that have shaped the diversification of a wide range of organisms, including plants (Liu et al ., 2015 ), fishes (Friedman et al ., 2019 ), mites (Kerschbaumer and Pfingstl, 2021 ) and parasites (Vignon et al ., 2011 ; Baillie et al ., 2019 ; Soares et al ., 2023a ). In Monogenoidea, different studies, using geometric morphometric data of the haptoral anchors, associated with molecular phylogenies have underscored the usefulness of this approach in tackling diverse evolutionary inquiries (Llopis-Belenguer et al ., 2015 ; Khang et al ., 2016 ; Rodríguez-González et al ., 2017 ; Rahmouni et al ., 2021 ; Soares et al ., 2023a ).…”
Section: Introductionmentioning
confidence: 99%